Synthesis, Characterization and Relativistic Dft Studies of Fac-Re(Co)3(Isonicotinic Acid)2cl Complex - Yanez-Sanchez, M (Elsevier B.V., 2017)
In this work, new fac-Re(CO)3(PyCOOH)2Cl from isonicotinic acid ligand has been prepared. The complex was characterized by structural (single-crystal X-ray diffraction), elemental analysis and spectroscopic (FTIR, NMR, UV–vis spectroscopy) methods. DFT and TDDFT calculations were performed to obtain the electronic transitions involved in their UV–Vis spectrum. The excitation energies agree with the experimental results. The TDDFT calculations suggest that experimental mixed absorption bands at 270 and 314 nm could be assigned to (MLCT-LLCT)/MLCT transitions. Natural Bond Orbitals (NBO) approach has enabled studying the effects of bonding interactions. E(2) energies confirm the occurrence of ICT (Intra-molecular Charge Transfer) within the molecule. © 2017 Elsevier B.V.